Establishing cross-curricular links between science and english in ninth grade (2003)
For many years, English has been studied apart from the other subjects in nonbilingual centres, isolating it from other knowledge areas, underestimating its nature as a vehicle for communication. English has thus been considered just as a set of rules to be memorized with no communicative purpose. As English teachers our objective to design this proposal, was to show this language as a useful tool, not only to be practiced in the classroom, but also in the context of other areas, in this case, science. Throughout the piloting of this project at Gustavo Restrepo school, in the south of Bogotá, English was used to learn science and science was used to practice English during the performance of some tasks with a communicative purpose so that the students of ninth grade had the opportunity to learn by doing. Key Words: English-High School-Teaching, Sciences-High School-Teaching, English-Teaching-Methods Por muchos años, el inglés ha sido estudiado aparte de las otras materias en instituciones no bilingües, aislándolo de otras áreas del conocimiento y menospreciando su naturaleza como vehículo de comunicación. El inglés ha sido entonces considerado simplemente un conjunto de reglas que se memorizan sin un propósito comunicativo. Como profesores de inglés nuestro objetivo al diseñar esta propuesta fue mostrar este idioma como una herramienta útil, no sólo para ser usada en el aula, sino también en el contexto de otras áreas; en este caso ciencias naturales. A través del pilotaje de este proyecto en el colegio Gustavo Restrepo en el sur de Bogotá, el inglés fue usado para aprender ciencias naturales y las ciencias naturales fueron usadas para practicar inglés durante el desarrollo de algunas actividades, con un propósito comunicativo de manera que los estudiantes de noveno grado tuvieran la oportunidad de aprender haciendo. Palabras claves: Inglés-Enseñanza Secundaria, Ciencias Naturales-Enseñanza Secundaria, Inglés-Enseñanza-Métodos